Bone tumors effective therapy through functionalized hydrogels: current developments and future expectations - Ruyi Shao; Yeben Wang; Laifeng Li; Yongqiang Dong; Jiayi Zhao; Wenqing Liang (Taylor & Francis Group, 2022)
Primary bone tumors especially, sarcomas affect adolescents the most because it originates from osteoblasts cells responsible for bone growth. Chemotherapy, surgery, and radiation therapy are the most often used clinical treatments. Regrettably, surgical resection frequently fails to entirely eradicate the tumor, which is the primary cause of metastasis and postoperative recurrence, leading to a high death rate. Additionally, bone tumors frequently penetrate significant regions of bone, rendering them incapable of self-repair, and impairing patients' quality of life. As a result, treating bone tumors and regenerating bone in the clinic is difficult. In recent decades, numerous sorts of alternative therapy approaches have been investigated due to a lack of approved treatments. Among the novel therapeutic approaches, hydrogel-based anticancer therapy has cleared the way for the development of new targeted techniques for treating bone cancer and bone regeneration. They include strategies such as co-delivery of several drug payloads, enhancing their biodistribution and transport capabilities, normalizing accumulation, and optimizing drug release profiles to decrease the limitations of current therapy. This review discusses current advances in functionalized hydrogels to develop a new technique for treating bone tumors by reducing postoperative tumor recurrence and promoting tissue repair.